STRATEGIES FOR COLLECTING AND DISTRIBUTING PRODUCTIVE ZAKAT TO INCREASE MUSTAHIK INCOME: A CASE STUDY OF BAZNAS BIMA CITY - Andri; Rafiuddin; Muh. Yunan (Jurnal Dinamika Ekonomi Syariah, 2025)
This study aims to analyze the strategies employed by BAZNAS Bima City in collecting and distributing productive zakat to increase mustahik income. It also explores the challenges faced and the corresponding solutions in the implementation process. Utilizing a qualitative method, the study is based on both primary and secondary data. Primary data were obtained through interviews, while secondary data were sourced from journals, books, and reports relevant to the topic. The findings reveal that BAZNAS Bima City plays a strategic role in enhancing mustahik welfare through systematic and sustainable zakat management. Despite operational obstacles, the institution has adopted innovations and engaged local stakeholders to address these issues. The study concludes that strengthening institutional capacity and partnerships is essential for optimizing the impact of productive zakat and achieving maqāṣid al-sharī‘ah.